2014
DOI: 10.1080/10942912.2014.884578
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical, and Thermogravimetric Characterization of Cellulosic By-Products Obtained from Biomass Seeds

Abstract: Rayón Encinas, E.; Ferrándiz Bou, S.; Rico Beneito, MI.; López Martínez, J.; Arrieta, MP. (2015). Microstructure, mechanical, and thermogravimetric characterization of cellulosic byproducts obtained from biomass seeds. International Journal of Food Properties. 18(6): 1211-1222. doi:10.1080/10942912.2014 Disclaimer: This is a version of an unedited manuscript that has been accepted for publication. As a service to authors and researchers we are providing this version of the accepted manuscript (AM). Copyeditin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…A matrix of 25 indentations at 1000 nm depth was performed on each sample. The indentation strain rate was 0.05 s −1 and depth correction of the surface contact was calculated by the Loubet method …”
Section: Methodsmentioning
confidence: 99%
“…A matrix of 25 indentations at 1000 nm depth was performed on each sample. The indentation strain rate was 0.05 s −1 and depth correction of the surface contact was calculated by the Loubet method …”
Section: Methodsmentioning
confidence: 99%
“…3, it can be clearly observed that the beginning of temperature of MPS was lower and the temperature range was wider than PS ascribed to the successful chemical modification by CA. Meanwhile, the third stage of the mass loss of PS ranged from 340 to 518℃ which can be attributed to the further pyrolysis of cellulose [27] . Comparing with PS, the temperature range of MPS at the third stage was wider than PS from 348 to 573℃ due to the further decomposition of the carboxyl groups introduced and cellulose.…”
Section: Thermogravimetric Analysis Of Ps and Mpsmentioning
confidence: 99%
“…Thus, the preparation of nanocomposites could be promising to achieve improvement in the properties of PHB. In this context, cellulose derivatives are optimal reinforcing materials for the bioplastic industry since they are bio‐based, biodegradable, stiff, lightweight, non‐abrasive to the processing equipment and highly abundant in nature at low cost . Nanocellulose shows a great variety of advantages such as extraordinary mechanical properties, reinforcing capabilities, low density, abundance and biodegradability …”
Section: Introductionmentioning
confidence: 99%